2018
DOI: 10.1242/dev.158543
|View full text |Cite
|
Sign up to set email alerts
|

The histone acetyltransferase inhibitor Nir regulates epidermis development

Abstract: In addition to its function as an inhibitor of histone acetyltransferases, Nir (Noc2l) binds to p53 and TAp63 to regulate their activity. Here, we show that epidermis-specific ablation of Nir impairs epidermal stratification and barrier function, resulting in perinatal lethality. Nir-deficient epidermis lacks appendages and remains single layered during embryogenesis. Cell proliferation is inhibited, whereas apoptosis and p53 acetylation are increased, indicating that Nir is controlling cell proliferation by l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…In addition to C40, TFAP2C binds within the first intron of TP63 , creating genome accessibility at these sites during epidermal commitment [83]. The histone acetyltransferase (HAT) inhibitor NOCL2 binds to P1 and P2 in keratinocytes and epidermal‐specific Nocl2 depletion increased H3K18 acetylation (H3K18Ac) and reduced ΔNp63 [97], contradicting the association of increased H3K18Ac levels with higher ΔNp63 in lung disease [98]. A role for histone methylation has also been reported, where loss of histone demethylase KMD6A activates a TP63 enhancer [99], related to monomethylation of H3K4 as a delimiter of super enhancer activity rather than to its role as a demethylase.…”
Section: Transcriptional Control Of P63mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to C40, TFAP2C binds within the first intron of TP63 , creating genome accessibility at these sites during epidermal commitment [83]. The histone acetyltransferase (HAT) inhibitor NOCL2 binds to P1 and P2 in keratinocytes and epidermal‐specific Nocl2 depletion increased H3K18 acetylation (H3K18Ac) and reduced ΔNp63 [97], contradicting the association of increased H3K18Ac levels with higher ΔNp63 in lung disease [98]. A role for histone methylation has also been reported, where loss of histone demethylase KMD6A activates a TP63 enhancer [99], related to monomethylation of H3K4 as a delimiter of super enhancer activity rather than to its role as a demethylase.…”
Section: Transcriptional Control Of P63mentioning
confidence: 99%
“…Indirect roles of acetylation have also been reported. NIR (NOC2L) was initially reported to bind TAp63 but not ΔNp63 [238], but subsequent work showed that it is associated with the TP63 locus and deletion reduces both histone acetylation and ΔNp63α levels [97]. In contrast, HDAC1/2 knockout did not alter ΔNp63α levels or ΔNp63α‐activated genes but induced ΔNp63‐repressed genes, associated with p63‐mediated targeting of HDAC1/2 to repressed gene promoters [239].…”
Section: Post‐translational Modifications That Influence P63 Protein Stability And/or Activitymentioning
confidence: 99%
“…However, epidermal ablation of either Hdac1 or Hdac2 did not affect epidermal development, suggesting these HDACs have redundant and compensatory functions. Similarly, epidermal deletion of HAT inhibitor Nir/Noc2l at E12.5 resulted in a single‐layered epidermis without stratification and impaired HF development in embryogenesis . Moreover, in vitro HDAC inhibition in human foreskin organ culture led to abnormal epidermal architecture, proliferation arrest, and premature terminal differentiation .…”
Section: Histone Acetylation In Skin Development and Homeostasismentioning
confidence: 99%
“…Moreover, NIR functions as a key regulator of skin development via controlling the expression of essential factors in epidermis development. 5 Previous studies have shown that NIR functions as a negative regulator of p53-dependent transcription by the direct interaction with p53. 4 NIR has also been shown to repress the expression of p63 by restricting H3K18ac at the p63 promoter.…”
Section: Introductionmentioning
confidence: 99%